(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract: The term "Marma" originates from the Sanskrit word "Mrin Maranae." The Sanskrit phrase "Mriyatae Asmin Iti Marma" means "there is a likelihood of death or serious damage to health when these points are afflicted." Therefore, these areas are referred to as marma. In Sanskrit, marma also means hidden or secret. Marma point is a juncture on the body where two or more types of tissues, such as muscles, veins, ligaments, bones, or joints, converge. The 107 Marma points are categorized based on various factors such as structure, region, dimension, and prognosis. Indrabasti Marma, located in both Shakha (extremities), has been characterized with a focus on its anatomical and surgical perspectives. The term "Indrabasti Marma" is derived from two words: "Indra," meaning prana (life force) or to reside in, and "basti," meaning to encase. Thus, Indrabasti Marma refers to the location where Prana resides. Its size, location, and the effects of injury (aaghata parinama) are mentioned in traditional texts. To apply the knowledge of Indrabasti Marma in the modern era, as described by the Acharyas, it is crucial to correlate it with contemporary anatomy, specifically considering the concept of the peripheral heart or calf muscle. This study aims to examine the Indrabasti Marma from a modern perspective, focusing on its relevance to the peripheral heart or calf muscle and related structures. Assistance is required to facilitate venous return, particularly when blood must overcome gravitational forces to flow from the lower extremities to the cardiac chambers. The soleus muscle assumes a pivotal role in actively propelling venous blood towards the heart from peripheral regions of the body. This study aims to establish the significance of Indrabasti Marma in relation to the peripheral heart by analysing the symptoms described as Viddhya Lakshan. Through cadaveric dissection, we seek to pinpoint its precise location and better understand its importance in this context.